The effects of attentional focus instructions on punching velocity and impact forces among trained combat athletes - Halperin, I.; Chapman, D. W.; Martin, D. T.; Abbiss, C. (Journal of Sports Sciences, 2017)
Research indicates that instructing athlete`s to focus on bodily movements (internal focus of attention [IFA]) may hinder performance, whereas instructing them to focus on the movement outcome (external focus of attention [EFA]) often enhances performance. Despite the importance of instructions in striking combat sports, limited research has examined the influence of IFA and EFA on performance in well-trained combat athletes. This study investigated the effects of different instructional cues on punching velocity (m /s) and normalised impact forces (N/kg) among intermediate (n = 8) and expert (n = 7) competitive boxers and kickboxers. Athletes completed three rounds of 12 maximal effort punches delivered to a punching integrator on three separate days. Day one was a familiarisation session with only control instructions provided. In the following two days athletes randomly received IFA, EFA or control instructions prior to each of the three rounds. Athletes punching with EFA were 4% faster and 5% more forceful than IFA (P < 0.05), and 2% faster and 3% more forceful than control (P < 0.05). Furthermore, experts punched 11% faster and with 13% greater force compared with intermediate athletes (P < 0.05). EFA led to a positive effect on punching performance and should be favoured over IFA and control instructions.